Neonatal Hypocalcemia in the Infant of a Diabetic Mother - Moss, Colleen Reilly (Neonatal network, 2020)
Neonatal hypocalcemia (NHC) is one of the most common disorders of calcium metabolism in infants admitted to the NICU. Presentation can range from asymptomatic to generalized seizures or tetany. In this case study, an infant with NHC is presented along with an overview of the pathophysiology, prevalence, diagnosis, and management of NHC for neonatal clinicians.Neonatal hypocalcemia (NHC) is one of the most common disorders of calcium metabolism in infants admitted to the NICU. Presentation can range from asymptomatic to generalized seizures or tetany. In this case study, an infant with NHC is presented along with an overview of the pathophysiology, prevalence, diagnosis, and management of NHC for neonatal clinicians.